Vaginal bleeding with multicystic ovaries and a pituitary mass in a child with severe hypothyroidism. (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S60-62The abstract of this article is available on the PubMed website